Charitable behavior in China under the Charity Law: Evaluation of charity advertisements involving in‐groups and out‐groups. Issue 3 (30th September 2020) - Suzuki, Satoko; Kohlbacher, Florian; Akutsu, Satoshi
Abstract : This paper examines Chinese charitable behavior in 2016—the year the Charity Law was enforced—with a focus on the evaluation of charity advertisements. The 2016 Charity Law is the first law in China to regulate charitable organizations and their activities. It also provides various tax incentives for charitable organizations and donors. A study was conducted to understand Chinese charitable behavior in terms of in‐groups and out‐groups. Results indicate that the Chinese more positively evaluate charity advertisements targeting in‐groups than those targeting out‐groups. This relationship between advertisement type and advertisement attitude is mediated by ethnocentrism. Furthermore, we found that familiarity with the Charity Law moderates the effect of ethnocentrism on advertisement attitude.